1995
DOI: 10.1161/01.atv.15.11.2019
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Gsand Inhibition of GiProtein Functions by Minimally Oxidized LDL

Abstract: We have previously shown that treatment of aortic endothelial cells with minimally oxidized LDL (MM-LDL) induces their interaction with monocytes but not neutrophils and that these induced responses are associated with increased cAMP levels. Here we studied the mechanism of by which MM-LDL elevates cAMP levels. Treatment of human aortic endothelial cells with MM-LDL resulted in a saturable dose-dependent increase in cAMP levels. Studies using a combination of pertussis toxin and MM-LDL suggested that part of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…Furthermore, exposure of Xenopus oocytes to PGPC did not desensitize the oocyte to the effect of POVPC (data not shown), supporting the hypothesis that the binding sites for the two molecules are different. We previously have reported that MM-LDL increased the levels of cAMP in human aortic endothelial cells by activation of a Gs-coupled receptor and decreasing the endogenous activation of a Gi-coupled receptor (7). The present studies demonstrate that POVPC, but not PGPC, activates a Gs-coupled pathway in Xenopus oocytes (Fig.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Furthermore, exposure of Xenopus oocytes to PGPC did not desensitize the oocyte to the effect of POVPC (data not shown), supporting the hypothesis that the binding sites for the two molecules are different. We previously have reported that MM-LDL increased the levels of cAMP in human aortic endothelial cells by activation of a Gs-coupled receptor and decreasing the endogenous activation of a Gi-coupled receptor (7). The present studies demonstrate that POVPC, but not PGPC, activates a Gs-coupled pathway in Xenopus oocytes (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…HAEC were incubated with oxidized phospholipids and͞or lipopolysaccharide (LPS) as for cell adhesion experiments, and total RNA was isolated from cells by using the guanidine thiocyanate͞phenol method. Northern blot analysis using E-selectin cDNA was performed as described (7). 36B4 or 28S cDNA were used to control for RNA loading.…”
Section: Measurement Of Campmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 Previous studies have suggested that scavenger receptors are unlikely to be the receptors that mediate MM-LDL-induced inflammatory responses in ECs. 34,42,43 Because they bind, internalize, and degrade oxLDL, scavenger receptors may influence accumulation of oxLDL in arterial walls.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work from our laboratory has shown that MM-LDL exerts its effects by initiating an increase in intracellular cAMP. 35 We therefore examined cAMP levels in the presence of IL-10 after stimulation with MM-LDL (Figure 3) or cholera toxin (data not shown) and found them to be elevated to levels equivalent to those in cells identically stimulated but not treated with IL-10. This study suggests that IL-10 acts downstream of the MM-LDL-mediated increase in cAMP.…”
Section: Il-10 Overexpression Reduces Atherosclerotic Lesion Developmmentioning
confidence: 98%